Less invasive plate osteosynthesis in humeral shaft fractures - Apivatthakakul T. (2014)
Objective Stable internal fixation of the humeral shaft by less invasive percutaneous plate insertion using two separate (proximal and distal) incisions, indirect reduction by closed manipulation and fixation to preserve the soft tissue and blood supply at the fracture zone. Early mobilization of the shoulder and elbow to ensure a good functional outcome. Indications Humeral shaft fractures (classified according to AO classification as: 12-A, B, C). Humeral shaft fractures extending to the proximal or distal shaft, small or deformed medullary canal or open growth plate. Contraindications Humeral shaft fractures with primary radial nerve palsy. Proximal humeral shaft fractures extending to the humeral head. Distal humeral fractures extending to the elbow joint. Surgical Technique Two incisions proximal and distal to the fracture zone are used. A 3-cm proximal incision lies between the lateral border of the proximal part of the biceps and the medial border of the deltoid. Distally, a 3-cm incision is made along the lateral border of the biceps. The interval between biceps and brachialis is identified. The biceps is retracted medially to expose the musculocutaneous nerve. The brachialis muscle has dual innervation, the medial half being innervated by the musculocutaneous nerve and the lateral half by the radial nerve. The brachialis is split longitudinally at its midline. The musculocutaneous nerve is retracted along with the medial half of the brachialis, while the lateral half of the brachialis serves as a cushion to protect the radial nerve. A deep subbrachial tunnel is created from the distal to the proximal incision. The selected plate is tied with a suture to a hole at the tip of the tunneling instrument for pulling the plate back along the prepared track. The plate is aligned in the correct position on the anterior surface of the humerus. Traction is applied and the fracture reduced to restore alignment by image intensifier, followed by plate fixation with at least two bicortical locking screws or three bicortical conventional screws in each fragment. Results Between January 2003 and January 2006, 23 patients were operated on using the less invasive plate osteosynthesis technique. The minimum follow-up period of 12 months was completed in 20 patients. The mean healing time was 14.6 weeks, defined as three of four cortices having stable bridging callus. In one patient with delayed union, healing was observed after 28 weeks. Functional outcomes were evaluated using the Constant Score and the Hospital for Special Surgery (HSS) Score. 19 patients had good to excellent elbow function with a mean HSS Score of 93.5 points. All patients achieved satisfactory shoulder function with a mean Constant Score of 85.8 points compared to 90.6 on the healthy side. Complications observed were one paresthesia of lateral cutaneous nerve of forearm (no radial nerve injury) and one loosening of the LCP (Locking Compression Plate) screws due to technical error. © Urban & Vogel.